2018
DOI: 10.1002/jnr.24339
|View full text |Cite
|
Sign up to set email alerts
|

Insights on UNC‐104‐dynein/dynactin interactions and their implications on axonal transport in Caenorhabditis elegans

Abstract: Bidirectional cargo transport in neurons can be explained by two models: the "tug-ofwar model" for short-range transport, in which several kinesin and dynein motors are bound to the same cargo but travel in opposing directions, and by the "motor coordination model" for long-range transport, in which small adaptors or the cargo itself activates or deactivates opposing motors. Direct interactions between the major axonal transporter kinesin-3 UNC-104(KIF1A) and the dynein/dynactin complex remains unknown. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 91 publications
(129 reference statements)
0
16
0
Order By: Relevance
“…Nevertheless, antibody staining after tag‐63 knockdown was significantly reduced (Figure D + E). Note that we have previously shown the efficiency of RNAi in neuronal tissues without the need of cross‐breeding with RNAi sensitive strains, and also for this study we provide data reflecting the efficiency of tag‐63 knockdown in neurons (Figure S8A + B). Though we have no information regarding the epitope sequence of the NFH200 antibody, we obtained the immunogen sequence for the NEFH antibody, and our analysis revealed that this antibody may cross‐react with TAG‐63, but likely not with IFP‐1, IFB‐1, or IFA‐4 (Figure S3B).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, antibody staining after tag‐63 knockdown was significantly reduced (Figure D + E). Note that we have previously shown the efficiency of RNAi in neuronal tissues without the need of cross‐breeding with RNAi sensitive strains, and also for this study we provide data reflecting the efficiency of tag‐63 knockdown in neurons (Figure S8A + B). Though we have no information regarding the epitope sequence of the NFH200 antibody, we obtained the immunogen sequence for the NEFH antibody, and our analysis revealed that this antibody may cross‐react with TAG‐63, but likely not with IFP‐1, IFB‐1, or IFA‐4 (Figure S3B).…”
Section: Resultsmentioning
confidence: 70%
“…As the disintegration of both vimentin and NFs are known to affect MT‐based transport, we analyzed the motility of kinesin‐3 UNC‐104 and its cargo SNB‐1 (synaptobrevin‐1) in ALM neurons of wild type, TAG‐63 knockout as well as TAG‐63 knockdown (RNAi) worms. Figure shows anterograde and retrograde velocity profiles of motor UNC‐104 as well as of its cargo SNB‐1, both tagged with mRFP (revealed from separate strains and experiments). Anterograde movements of UNC‐104 are reduced in tag‐63 ( ok471 ) animals (Figure A + D) pointing toward a regulatory role of TAG‐63 on UNC‐104's motor activity.…”
Section: Resultsmentioning
confidence: 99%
“…6B). However, it needs to be noted that UNC-104 may exist in complexes with dynein [12] or that multiple motors of different directionalities (antagonistic motors) may accumulate and bind to the same cargo vesicle resulting in saltatory movements of that vesicle. Because we only observe the movements of fluorescent UNC-104 particles, we may expect that we measure either moving parameters of single motors or those of multiple motors accumulated on a single vesicle.…”
Section: Ptp-3 Knockout Results In Increased Anterograde Motor and Camentioning
confidence: 99%
“…2) Cargo binding activates kinesins [11]. 3) Physical pulling via opposing motor dynein activates kinesins [12]. 4) Binding of small adaptor proteins such as SYD-2 and LIN-2 activates kinesin [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the "tug-of-war" model proposed in in vitro and cell culture studies (Hancock, 2018). Conversely, UNC-104 has also been reported to physically interact with several components of the Dynein-Dynactin complex, such as DYLT-1, DYRB-1, DNC-5 and DNC-6, which have been shown to affect the velocity and dwell times of UNC-104 along the neuronal process and the anterograde transport of SNB-1 in C. elegans neurons (Chen et al, 2019). It has further been proposed that these interactions are necessary to activate UNC-104, promote anterograde axonal transport (Chen et al, 2019), and likely function to localize components of the retrograde transport machinery to distal tips of neuronal processes (Figure 2(a)).…”
Section: Regulators Of Retrograde Axonal Transportmentioning
confidence: 99%